2022
DOI: 10.1111/ina.13077
|View full text |Cite
|
Sign up to set email alerts
|

Identification of high radon dwellings, risk of exposure, and geogenic potential in the mining area of the “TREPČA” complex

Abstract: This study was performed to investigate radon levels in dwellings in the mining area near the town of Kosovska Mitrovica. The Passive radon technique based on the charcoal canister test kit conducted in summer and autumn 2019 showed unexpected results. The reference level of 300 Bq/m3 for indoor radon concentration was exceeded in 15 of 26 dwellings. Preliminary measurements of gamma dose rate in some dwellings built from local stone showed values from 0.30 to 0.45 μSv/h, while 75% of measurements in dwellings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…In addition, high indoor radon in this house may be affected by the proximity of a deep fault zone that allows the radon transport through cracks of permeable soil, as well as the higher porosity of sand and gravel of the river bank that allows increased radon diffusion. All of the results confirmed that this is a radon prone area (RPA), as reported by a recent study [64].…”
Section: Indication Of Radon Prone Areasupporting
confidence: 90%
“…In addition, high indoor radon in this house may be affected by the proximity of a deep fault zone that allows the radon transport through cracks of permeable soil, as well as the higher porosity of sand and gravel of the river bank that allows increased radon diffusion. All of the results confirmed that this is a radon prone area (RPA), as reported by a recent study [64].…”
Section: Indication Of Radon Prone Areasupporting
confidence: 90%
“…Limited studies have directly provided RR as the effect size the lung cancer by indoor radon exposures. Meanwhile, there are well-designed radon studies with large-scale exposure data, [61][62][63][64][65] new predicting model, 66 geometric tools, and survey protocol development in other regions. 67,68 Current results from the reviewed literature were mainly focusing on populations from urban areas especially those from regions other than China.…”
Section: Discussionmentioning
confidence: 99%
“…These detectors are typically left in the environment for several months to accumulate sufficient data for analysis.• Charcoal canisters are another type of passive detector that can be used to measure radon concentration. 38 These detectors consist of a small container filled with activated charcoal that absorbs radon and its decay products. The canisters are left in the environment for a certain period, after which they are sent to a laboratory for analysis.• Electret ion chambers are another type of passive detector that can be used to measure radon concentration.…”
Section: Indoor Rn Assessmentmentioning
confidence: 99%
“…• Charcoal canisters are another type of passive detector that can be used to measure radon concentration. 38 These detectors consist of a small container filled with activated charcoal that absorbs radon and its decay products. The canisters are left in the environment for a certain period, after which they are sent to a laboratory for analysis.…”
Section: Indoor Rn Assessmentmentioning
confidence: 99%